Preservation of Conclusion Temple With "Historic Urban Landscape" Technique in The Islamic Indonesia University Environment - Rahmat Firdaus Bouty; Arif Budi Sholihah; Putu Ayu Pramanasari Agustiananda (International Journal of Architecture and Urbanism, 2019)
Mataram civilization is a Hindu-Buddhist civilization. In the ancient Mataram kingdom, many buildings or artifacts were built for ceremonies such as the temple. One of them is Kecah Temple or Pustakala Temple located in the Indonesian Islamic University (UII). The temple itself was built by a group of people around who were relics in the 9th - 10th century AD. This temple was discovered during the construction of the Library Building on December 9, 2009 which was then excavated by the Archaeological Heritage Preservation Hall (BP3K), in this temple there is a statue of God Ganesha which is interpreted as the god of intelligence and knowledge, which is very suitable for the Library Building gain knowledge. The existence of this temple is very guarded by the campus because UII is the only campus in Indonesia that has temples in the campus environment. However, this temple still lacks info about its original and historical name. The approach technique applied from the topic of "Urban Landscape Heritage" is the technique of preservation of Social Cohesion. In accordance with the definition of social cohesion, so that this building or temple can be maintained according to its function in the future, it is necessary to involve the opinions of visitors or respondents from the research. The research method used was observation and interviews of visitors to the library and the concluding temple museum to obtain statistical data and to study restoration techniques in the temple. The purpose of the study is to be able to find out information relating to the temple. Conclusion from the visitors about the concluding temple and review whether this temple is still suitable for use by Hindus as a ceremonial process or not. The results of the study can find a function of the Conclusion Temple which can be adapted to socio-cultural values ​​so as to uphold tolerance of social values. Keyword: Kimpulan temple, Library, Universitas Islam Indonesia, Preservation.